Comparison of minimum space allowance standards for transportation of cattle by road from 8 authorities. - Whiting, T L (2000)
Space allowance for animals in transit is a consistent concern in many countries developing codes of practice and regulations to assure humane treatment of food producing animals. Describing minimum space allowance requirements for cattle in transit has proven to be difficult, as the space required increases as the animal grows. Loading pressure, defined as weight of live animal per unit area, has proven to be a clear method of communicating with transporters and inspection staff what the maximum safe stocking limit is based on individual animal weight. The loading density recommendations in the Canadian code of practice for beef cattle are compared with other standards by using loading pressure charts as a visual aid. Loading pressure charts are recommended in preference to a tabular format to describe the minimal space allowed per animal for cattle transported by road.